Dynamic Nuclear Polarization‐Enhanced Biomolecular NMR Spectroscopy at High Magnetic Field with Fast Magic‐Angle Spinning. (27th April 2018) - Jaudzems, Kristaps; Bertarello, Andrea; Chaudhari, Sachin R.; Pica, Andrea; Cala‐De Paepe, Diane; Barbet‐Massin, Emeline; Pell, Andrew J.; Akopjana, Inara; Kotelovica, Svetlana; Gajan, David; Ouari, Olivier; Tars, Kaspars; et al.
Abstract: Dynamic nuclear polarization (DNP) is a powerful way to overcome the sensitivity limitation of magic‐angle‐spinning (MAS) NMR experiments. However, the resolution of the DNP NMR spectra of proteins is compromised by severe line broadening associated with the necessity to perform experiments at cryogenic temperatures and in the presence of paramagnetic radicals. High‐quality DNP‐enhanced NMR spectra of the Acinetobacter phage 205 (AP205) nucleocapsid can be obtained by combining high magnetic field (800 MHz) and fast MAS (40 kHz). These conditions yield enhanced resolution and long coherence lifetimes allowing the acquisition of resolved 2D correlation spectra and of previously unfeasible scalar‐based experiments. This enables the assignment of aromatic resonances of the AP205 coat protein and its packaged RNA, as well as the detection of long‐range contacts, which are not observed at room temperature, opening new possibilities for structure determination.